2022
DOI: 10.1371/journal.pone.0267855
|View full text |Cite
|
Sign up to set email alerts
|

Blockade of p38 MAPK overcomes AML stem cell line KG1a resistance to 5-Fluorouridine and the impact on miRNA profiling

Abstract: Most of the AML patients in remission develop multidrug resistance after the first-line therapy and relapse. AML stem cells have gained attention for their chemoresistance potentials. Chemoresistance is a multifactorial process resulting from altered survival signaling pathways and apoptosis regulators such as MAPK, NF-κB activation and ROS production. We targeted the survival pathway p38 MAPK, NF-κB and ROS generation in human chemoresistant AML stem cell line KG1a, susceptible to enhance cell sensitivity to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 65 publications
3
11
2
Order By: Relevance
“…The activation of the p38 MAPK pathway plays a critical role in orchestrating a range of cellular stresses, growth, and survival of tumor cells. , p38 MAPK is often increased and/or overactivated in AML blasts and represents an important pharmacological target. However, selective p38 MAPK inhibitors have limited efficacy and for a variety of clinical indications none have progressed to Phase III . Losmapimod (known as GW856553 or GSK-AHAB) is a selective, potent, and orally MAPK14 (p38α MAPK) ATP competitive inhibitor used in several clinical trials (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…The activation of the p38 MAPK pathway plays a critical role in orchestrating a range of cellular stresses, growth, and survival of tumor cells. , p38 MAPK is often increased and/or overactivated in AML blasts and represents an important pharmacological target. However, selective p38 MAPK inhibitors have limited efficacy and for a variety of clinical indications none have progressed to Phase III . Losmapimod (known as GW856553 or GSK-AHAB) is a selective, potent, and orally MAPK14 (p38α MAPK) ATP competitive inhibitor used in several clinical trials (Table S1).…”
Section: Resultsmentioning
confidence: 99%
“…39,40 p38 MAPK is often increased and/or overactivated in AML blasts and represents an important pharmacological target. [41][42][43] However, selective p38 MAPK inhibitors have limited efficacy and for a variety of clinical indications none have progressed to Phase III. 44 Losmapimod (known as GW856553 or GSK-AHAB) is a selective, potent, and orally MAPK14 (p38α MAPK) ATP competitive inhibitor 45 (Figure 1A) used in several clinical trials (Table S1).…”
Section: Experimental Overviewmentioning
confidence: 99%
“…The cellautonomous role of the p38 MAPK signaling pathway in myeloid leukemia is also under investigation. Matou-Nasri et al (2022) underscored the role of the p38 MAPK pathway in the survival of AML cells.…”
Section: Regulation Of Normal and Dysregulated Hematopoiesis Via Cell...mentioning
confidence: 99%
“…The cell‐autonomous role of the p38 MAPK signaling pathway in myeloid leukemia is also under investigation. Matou‐Nasri et al (2022) underscored the role of the p38 MAPK pathway in the survival of AML cells. They showed that treating KG1a cells with SB202190, a p38 MAPK inhibitor, promoted apoptosis of the LCs and increased their sensitivity toward 5‐fluorouridine (Matou‐Nasri et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation